Determination of Some Oxidative Stress Parameters and Antioxidants in Sample of Iraqi Beta Thalassemia Major Patients - Ahmed , Amna K.; Yenzeel, Jabbar H. (Iraqi Journal of Science, 2022)
Repeated blood transfusion in beta thalassemia major patients may lead to peroxidative tissue injury by secondary iron overload. In the present study, 100 patients(50 male+50 female) with beta thalassemia major patients with age (5-20) years and 60 healthy control were included during their attendance at Abin Al_Baladi hospital in Baghdad. Malondialdehyde ,Superoxide Dismutase and Vitamin E, were measured by using kits.The results showed A highly significant (p<0.01)increase in the levels of Malondialdehyde and Superoxide Dismutase, whereas, significant p(<0.01)decrease in the levels of vitamin-E, This suggest that oxidative stress and reduced antioxidant defense mechanism play an important role in pathogenesis of beta thalassemia major.